Clinical Characteristics and Risk Factors of Recurrent Lumbar Disk Herniation: A Retrospective Analysis of Three Hundred Twenty-One Cases. Issue 21 (1st November 2018) - Li, Zhonghai; Yang, Hao; Liu, Mozhen; Lu, Ming; Chu, Jin; Hou, Shuxun; Hou, Tiesheng
Abstract : Study Design: Retrospective clinical series. Objective: To investigate the clinical features and the risk factors for recurrent lumbar disc herniation (rLDH) in China. Summary of Background Data: rLDH is a common cause of poor outcomes after lumbar microdiscectomy surgery. Risk factors for rLDH are increasingly being investigated. However, results in these previous studies were not always consistent. Methods: Between June 2005 and July 2012, 321 consecutive patients with single-level LDH, who underwent surgery, were enrolled in this study. We divided the patients into the recurrent group (R group) and the nonrecurrent group (N group) and compared their clinical parameters and preoperative radiologic parameters. The relationships between the variables and rLDH were evaluated by univariate analysis and multiple logistic regression analysis. Results: There was significant difference between groups in sex ( P  = 0.003), age ( P  = 0.003), current smoking ( P  = 0.004), body mass index (BMI) ( P  = 0.04), occupational lifting ( P  < 0.001), trauma history ( P  = 0.04), procedures ( P  = 0.04), herniation type ( P  = 0.006), disc height index (DUI) ( P  = 0.04), facet orientation (FO) ( P  = 0.04), facet tropism (FT) ( P  = 0.04), and sagittal range of motion (from) ( P  = 0.04). By putting these differences in logistic regression analysis, it showed that being male, young age, current smoking, higher BMI, herniation type (transligamentous extrusion), surgical procedures (bilateral laminectomy or total laminectomy), heavy works, undergoing a traumatic event, a large from, a high DUI, a large FT, and a small FO significantly related with rLDH. Conclusion: Based on our data, sex, age, current smoking, BMI, occupational lifting, trauma, surgical procedures, herniation type, DUI, FO, FT, and from showed a significant correlation with the incidence of rLDH. Patients with these risk factors should be paid more attention for prevention of recurrence after primary surgery. Level of Evidence: 3